Ancient magic and ritual power - Meyer, Marvin W.; Mirecki, Paul Allan (Religions in the Graeco-Roman world, 1995)
Preliminary material /Marvin Meyer and Paul Mirecki -- INTRODUCTION /Marvin Meyer and Paul Mirecki -- TRADING PLACES /Jonathan Z. Smith -- EXCLUDING THE CHARMING: THE DEVELOPMENT OF THE GREEK CONCEPT OF MAGIC /Fritz Graf -- THE RELIGIOUS, SOCIAL, AND LEGAL PARAMETERS OF TRADITIONAL EGYPTIAN MAGIC /Robert K. Ritner -- HITTITE MILITARY RITUALS /Richard H. Beal -- RITUAL MEALS IN THE HITTITE CULT /Billie Jean Collins -- MAGICAL USES OF ANCIENT MESOPOTAMIAN FESTIVALS OF THE DEAD /J. A. Scurlock -- THE \'WITCH\' OF EN-DOR, 1 SAMUEL 28, AND ANCIENT NEAR EASTERN NECROMANCY /Brian B. Schmidt -- THE MAGICIAN AS OUTSIDER IN THE HEBREW BIBLE AND THE NEW TESTAMENT /Stephen D. Ricks -- CHARMING CRIMINALS: CLASSIFICATION OF MAGIC IN THE BABYLONIAN TALMUD /Jonathan Seidel -- MAGICAL PIETY IN ANCIENT AND MEDIEVAL JUDAISM /Michael D. Swartz -- THE ADJURATION OF THE PRINCE OF THE PRESENCE: PERFORMATIVE UTTERANCE IN A JEWISH RITUAL /Rebecca Lesses -- NEW GREEK MAGICAL AND DIVINATORY TEXTS IN BERLIN /William M. Brashear -- GREEK EXORCISTIC AMULETS /Roy Kotansky -- SUPERNATURAL ASSISTANTS IN THE GREEK MAGICAL PAPYRI /Leda Jean Ciraolo -- THE MYSTODOKOS AND THE DARK-EYED MAIDENS: MULTICULTURAL INFLUENCES ON A LATE-HELLENISTIC INCANTATION /Christopher A. Faraone -- \'MAY SHE NEITHER EAT NOR DRINK\': LOVE MAGIC AND VOWS OF ABSTINENCE /David Martinez -- DEFINING THE DREADFUL: REMARKS ON THE GREEK CHILD-KILLING DEMON /Sarah Iles Johnston -- SINGING AWAY SNAKEBITE: LUCAN'S MAGICAL CURES /Oliver Phillips -- SATAN'S FALL IN COPTIC MAGIC /Jacques van der Vliet -- MAGICAL BOWLS AND MANICHAEANS /Jason David BeDuhn -- MAGIC, WOMEN, AND HERESY IN THE LATE EMPIRE: THE CASE OF THE PRISCILLIANISTS /Todd Breyfogle -- NARRATING POWER: THE THEORY AND PRACTICE OF THE MAGICAL HISTORIOLA IN RITUAL SPELLS /David Frankfurter -- PLATES: NEW GREEK MAGICAL AND DIVINATORY TEXTS IN BERLIN /Marvin Meyer and Paul Mirecki.